I support this answer it’s correct I see it ♥️
Hello There!
Write out your equation:
![(a^3 - b)/c](https://tex.z-dn.net/?f=%28a%5E3%20-%20b%29%2Fc)
Substitute the values in:
![(3^3 - 2)/4](https://tex.z-dn.net/?f=%283%5E3%20-%202%29%2F4)
Simplify:
![(27 - 2)/4](https://tex.z-dn.net/?f=%2827%20-%202%29%2F4)
![25/4](https://tex.z-dn.net/?f=25%2F4)
Solve:
It is 6.25.
Therefore, your answer is
6 1/4.
Hope This Helps You!Good Luck :)
- Hannah ❤
<u><em>Question 28:</em></u>
Subtract
on both sides
Divide
on both sides
<u><em>*(Answer)*=</em></u> ![\frac{S-2\pi r^2}{2\pi r} =h](https://tex.z-dn.net/?f=%5Cfrac%7BS-2%5Cpi%20r%5E2%7D%7B2%5Cpi%20r%7D%20%3Dh)
<u><em>Question 30:</em></u>
Multiply
on both sides
Subtract
on both sides
<u><em>*(Answer)*=</em></u> ![a*t+v_{0} =v_{1}](https://tex.z-dn.net/?f=a%2At%2Bv_%7B0%7D%20%3Dv_%7B1%7D)
Hope This Helps
BangtanBoyScouts
Answer:
![\displaystyle x=-\frac{1}{6}, 3](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D-%5Cfrac%7B1%7D%7B6%7D%2C%203)
Step-by-step explanation:
Hi there!
![y = 6x^2 - 17x - 3](https://tex.z-dn.net/?f=y%20%3D%206x%5E2%20-%2017x%20-%203)
Factor by grouping:
![y = 6x^2 - 18x+1x - 3\\y = 6x(x- 3)+1x - 3\\y = 6x(x- 3)+(x - 3)\\y = (6x+1)(x- 3)](https://tex.z-dn.net/?f=y%20%3D%206x%5E2%20-%2018x%2B1x%20-%203%5C%5Cy%20%3D%206x%28x-%203%29%2B1x%20-%203%5C%5Cy%20%3D%206x%28x-%203%29%2B%28x%20-%203%29%5C%5Cy%20%3D%20%286x%2B1%29%28x-%203%29)
Let y=0. Apply the zero product property:
![0 = (6x+1)(x- 3)](https://tex.z-dn.net/?f=0%20%3D%20%286x%2B1%29%28x-%203%29)
![6x+1=0\\6x=-1\\\\\displaystyle x=-\frac{1}{6}](https://tex.z-dn.net/?f=6x%2B1%3D0%5C%5C6x%3D-1%5C%5C%5C%5C%5Cdisplaystyle%20x%3D-%5Cfrac%7B1%7D%7B6%7D)
AND
![x-3=0\\x=3](https://tex.z-dn.net/?f=x-3%3D0%5C%5Cx%3D3)
I hope this helps!
Answer:
D
Step-by-step explanation: